Microalgae biotechnology as a promising pathway to ecofriendly aquaculture: a state‐of‐the‐art review. Issue 4 (16th December 2020) - Li, Huankai; Chen, Sihua; Liao, Kang; Lu, Qian; Zhou, Wenguang
Abstract: Aquaculture is an important industry providing high‐quality animal protein to humans, but it brings serious environmental pollutions, such as eutrophication of water bodies and the abuse of antibiotics. Microalgae cultivation, which can recover nutrients, release oxygen and yield value‐added biomass, has been studied intensively as a promising biotechnology for aquaculture wastewater treatment and fish diet production. Herein, we introduce a novel concept of applying microalgae biotechnology in aquaculture by integrating wastewater remediation, biomass harvesting and aquatic animals rearing systems. We review recent progress in aspects of value‐added algal species screening, algae cultivation systems design, nutrient recovery by algal–bacterial interactions, and biomass harvesting technologies. Finally, we discuss some problems, including bacterial contamination, unfavorable conditions in effluent and lack of technological assessment, which may hinder the application of microalgae biotechnology. It is expected that this paper could attract researchers' and technicians' attention to the microalgae‐based pollution control and promote the development of ecofriendly aquaculture. © 2020 Society of Chemical Industry